The Implementation of Information Services in the Prevention of Drugs Abuse in School - Meisari Meisari; Saiful Akhyar Lubis; Abdurrahman Abdurrahman (Jurnal Basicedu, 2022)
This study aims to describe the implementation of information services in the context of preventing drug abuse in schools. The type of this research is a qualitative approach with a descriptive study method. Informants in this study included school principals, deputy principals, heads of administrative affairs, counseling guidance teachers (counselors), and students. The research was carried out for 3 (three) consecutive months, namely June, July, and August 2021. The research data will be tested for credibility through diligent observation, triangulation, discussing research results, adequacy of references, and analysis of research cases. The results show that the implementation of information services in the context of preventing narcotics abuse in schools includes aspects of information service material (understanding, types, and factors of narcotics abuse) and information service methods (lectures, discussions, questions and answers, and the use of guide books). Supporting this implementation, it is hoped that there will be a strengthening of the concept and consistency of counselors (supervising teachers) and peer tutors in equipping students with insights, knowledge, skills, values and attitudes in implementing these information services through the effectiveness of training and deepening of information material.